Treatment outcome definitions in nontuberculous mycobacterial pulmonary disease: an NTM-NET consensus statement. Issue 3 (22nd March 2018) - van Ingen, Jakko; Aksamit, Timothy; Andrejak, Claire; Böttger, Erik C.; Cambau, Emmanuelle; Daley, Charles L.; Griffith, David E.; Guglielmetti, Lorenzo; Holland, Steven M.; Huitt, Gwen A.; Koh, Won-Jung; Lange, Christoph; et al.
Nontuberculous mycobacterial pulmonary diseases (NTM-PD) are increasingly recognised as opportunistic infections of humans. These chronic pulmonary infections have two main presentations. The first is a fibro-cavitary disease, that occurs in patients with pre-existing pulmonary diseases, such as chronic obstructive pulmonary disease, bronchiectasis, previous tuberculosis or other structural lung disease. The second presentation is a nodular-bronchiectatic disease of primarily the lingula and middle lobe that tends to affect a middle-aged and elderly female population [1]. Improving treatment outcome reporting in NTM disease: NTM-NET (@ntmnet) consensus statement on treatment outcome definitions http://ow.ly/c6IC30iwLM4